2023
DOI: 10.3389/fonc.2022.966441
|View full text |Cite
|
Sign up to set email alerts
|

The BET inhibitor/degrader ARV-825 prolongs the growth arrest response to Fulvestrant + Palbociclib and suppresses proliferative recovery in ER-positive breast cancer

Abstract: Anti-estrogens or aromatase inhibitors in combination with cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitors are the current standard of care for estrogen receptor-positive (ER+) Her-2 negative metastatic breast cancer. Although these combination therapies prolong progression-free survival compared to endocrine therapy alone, the growth-arrested state of residual tumor cells is clearly transient. Tumor cells that escape what might be considered a dormant or quiescent state and regain proliferative capacity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 75 publications
(101 reference statements)
6
27
1
Order By: Relevance
“…These results are, in part, consistent with data from our laboratory, where we investigated the potential utilization of ARV-825 as a senolytic in ER+ breast cancer models [38]. Initially, senescence was induced in both MCF-7 and T47D cells using a combination of fulvestrant plus palbociclib (F+P), as confirmed by beta-galactosidase staining and the quantification of senescence using C 12 FDG, a beta-galactosidase florescent metabolite, as well as by monitoring SASP markers.…”
Section: The Contribution Of Autophagy To Senolysis Mediated By Bet I...supporting
confidence: 90%
See 2 more Smart Citations
“…These results are, in part, consistent with data from our laboratory, where we investigated the potential utilization of ARV-825 as a senolytic in ER+ breast cancer models [38]. Initially, senescence was induced in both MCF-7 and T47D cells using a combination of fulvestrant plus palbociclib (F+P), as confirmed by beta-galactosidase staining and the quantification of senescence using C 12 FDG, a beta-galactosidase florescent metabolite, as well as by monitoring SASP markers.…”
Section: The Contribution Of Autophagy To Senolysis Mediated By Bet I...supporting
confidence: 90%
“…Consistent with the differential sensitivity observed, the SKOV-3 and HEY cells demonstrated a higher apoptosis response as compared to the A2780 and HO-8910 cell lines, in a dose-dependent manner. BRD4 and c-Myc levels were downregulated in the four cell lines upon JQ1 treatment, as would have been expected considering that these are established downstream targets of JQ1 and other BET inhibitors [38,48].…”
Section: Ovarian Cancersupporting
confidence: 62%
See 1 more Smart Citation
“…Finnegan et al. found that inhibiting autophagy with chloroquine and bafilomycin A1 and silencing the autophagy-regulating gene ATG5 did not sensitize Fulvestrant + Palbociclib to breast tumor cells, indicating that in breast tumors, the autophagy mechanism is non-protective under the action of Fulvestrant + Palbociclib ( 41 ). In summary, different anti-tumor drugs play their respective important roles by altering autophagy mechanisms under different conditions.…”
Section: Autophagy and Endometrial Cancermentioning
confidence: 99%
“…The most frequently utilized CDKi, usually in combination with either fulvestrant or letrazole, is palbociclib ( 130 , 169 ). Palbociclib is a potent inducer of the senescence phenotype; for example, Jost et al.…”
Section: Senescence and Breast Cancer Cell Survivalmentioning
confidence: 99%